Penerapan Pasal 3 Undang-Undang Nomor 31 Tahun 1999 Tentang Pemberantasan Tindak Pidana Korupsi Sebagaimana Telah Diubah Dengan Undang-Undang Nomor 20 Tahun 2001 Tentang Perubahan Atas Undang-Undang Nomor 31 Tahun 1999 Tentang Pemberantasan Tindak Pidana Korupsi Terhadap Tindak Pidana Perpajakan (Analisis Putusan Pengadilan Tindak Pidana Korupsi pada Pengadilan Negeri Medan Nomor: 02/Pid.Sus-TPK/2015/PN.Mdn - Haq, Dara Jayanita; Indra, Mexsasai; ', Erdiansyah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2017)
Corruption is sub-ordination to the public interest for personal goals that include violations of norms, onus, and general well-being, accompanied with secrecy, betrayal, deception, and unconcerned about suffering of the communities. Tax crime is an act that violates the laws which give rise to state loses tax revenue which the person is threatened with criminal penalties. Corruption is lex specialist derogat legi generali so that corruption cases should be examined based on the laws of corruption. Tax crime is lex specialist systematic, so tax crime case must be examined and decided upon by the tax laws. A tax levied by the Civil Service but not paid to the state treasury is more specific crime of corruption. Legal certainty is required to define more precise rules to be applied uniformly.Application of the Article 3 of Law Number 31 of 1999 on Corruption Act as amended by Act Number 20 of 2001 on the Amendment Act Number 31 of 1999 on Corruption Eradication in the decision No. 02/Pid.Sus-TPK/2015/PN.Mdn at the Corruption Court on Medan District Court is not appropriate for violating the principle of lex specialist systematic, and tax crime can be qualified as criminal acts of corruption as defined in Article 3 of Law Number 31 of 1999 on Corruption Act as amended by Act Number 20 of 2001 on the Amendment of Act Number 31 of 1999 on the Eradication of Corruption.